Molecular and Microscopic-Based Characterization of Plasmodium spp. in Fars and Hormozgan Provinces, South of Iran - Tahereh Mohammadzadeh; Gholamreza Hatam; Mohsen Kalantari; Bahador Sarkari; Mohammad Hosein Motazedian; Seyed Mahmoud Sadjjadi; Reza Safari (Journal of Tropical Medicine)
Despite malaria control programs in recent years, malaria transmission has not been eliminated in Iran. Molecular techniques including PCR, which has proved more sensitive and specific than microscopic examination methods, help to detect infection in low levels of parasitemia and mixed infections. Main our objectives were setting up nested PCR for detection of malaria and evaluating PCR based on plasmodia DNA from blood smears in Fars province, the comparison of this method with traditional microscopy and also evaluate the data in comparison with its neighboring province, Hormozgan. A total of 149 malaria positive samples including 116, 19, and 14 samples from Shiraz, Jask, and Lengeh ports were utilized in this study, respectively. Blood slides were prepared for microscopic observation. DNA from thin smears was extracted and nested PCR was analyzed using rPLU5 and rPLU6 for genus specification, rFAL1, rFAL2, and rVIV1, rVIV2 for P. falciparum and P. vivax detection, respectively. The results showed that 126 (84.6%), 16 (10.7%), and 7 (4.7%) out of 149 cases were positive for P. vivax, P. falciparum, and mixed infections, respectively, by microscopy. The PCR indicated that 95 (63.7%), 15 (10.1%), and 22 (14.8%) cases were infected with P. vivax, P. falciparum, and mixed mentioned species, respectively, and 17 (11.4%) cases were uninfected. Our results confirmed the considerable sensitivity of nested PCR for detection of the mixed infections. Simultaneous application of PCR even based on microscopy slides can facilitate access to the highest level of confidence in malaria researches.